Proposing Game Concepts and Design Recommendations for Minority Language Learning: Karelian Language - Tanskanen, Petri; Arhippainen, Leena (Zenodo, 2020)
Revitalizing endangered minority languages is important. Learning games and gamified application could provide potential ways to support learning of minority languages and their dialects. We present the findings from evaluations made for the popular learning games and Karelian language learning games. Based on the results, new concepts and design recommendations are presented for minority language learning game development, especially in Karelian language context.